2008
DOI: 10.1007/s10764-007-9224-7
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Taxonomy and Diversification of Leontopithecus using the Mitochondrial Control Region

Abstract: Leontopithecus comprises 4 taxa: black lion tamarins (L. chrysopygus), golden lion tamarins (L. rosalia), black-faced lion tamarins (L. caissara), and golden-headed lion tamarins (L. chrysomelas). Endemic to the Atlantic Forest of Brazil, they are endangered (Appendix I, CITES; IUCN Critically Endangered: Leontopithecus chrysopygus, L. caissara; IUCN Endangered: L. rosalia, L. chrysomelas). The 4 taxa are differentiated morphologically and geographically and occupy different habitat types. However, it is not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…We find that this species is most closely related to the black lion tamarin based on the high level of sequence identity. This finding is consistent with prior taxonomic studies using genetics and morphology, which found the two species to be closely related (Perez-Sweeney et al 2008;Mundy and Kelly 2001;Rosenberger and Coimbra-Filho 2008). We confirm the pattern of diverging mutations falls mostly within the non-coding D-loop.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…We find that this species is most closely related to the black lion tamarin based on the high level of sequence identity. This finding is consistent with prior taxonomic studies using genetics and morphology, which found the two species to be closely related (Perez-Sweeney et al 2008;Mundy and Kelly 2001;Rosenberger and Coimbra-Filho 2008). We confirm the pattern of diverging mutations falls mostly within the non-coding D-loop.…”
Section: Introductionsupporting
confidence: 92%
“…The sister taxa relationship between these species had been under debate until 2001 when photoreceptor intron sequences unambiguously established their relationship (Mundy and Kelly 2001). In, 2008 the first mitochondrial sequences, of the D-loop, confirmed their close relationship (Perez-Sweeney et al 2008). We extend this evidence by showing near perfect synteny throughout the coding regions.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The black-faced lion tamarin ( Leontopithecus caissara ), whose specific status has recently received support from molecular data ( Perez-Sweeney et al , 2008 ), is a critically endangered Neotropical primate ( Kierulff et al , 2008 ). Its distribution range lies in lowland swampy forests of southeastern Brazil ( Lorini and Persson, 1994 ), with a population currently estimated at less than 500 individuals (A. Nascimento, pers comm).…”
mentioning
confidence: 99%
“…The Leontopithecus are small neotropical primates belonging to the Callitrichidae family, infraorder Platyrrhini, and suborder Haplorhini. Currently, there are four known species of Lion Tamarin: Golden‐headed Lion Tamarin ( Leontopithecus chrysomelas ), Black Lion Tamarin Leontopithecus chrysopygus ), Golden Lion Tamarin ( Leontopithecus rosalia ), and a new species depicted, Superagui Lion Tamarin (Black‐faced Lion Tamarin), that would be a subspecies of the Leontopithecus chrysopygus , but of which other authors have concluded that is a valid species.…”
Section: Introductionmentioning
confidence: 99%